Implementation of Differentiated Instruction in the Indonesian Language Course: Lecturer Strategies in Accommodating Gen Z Learning Styles - Mahendra Aswit Sandra Barata Publik (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study presents an analysis of the implementation of differentiated learning in Indonesian Language courses at the university level. The main focus of the study is to uncover lecturers’ operational strategies in accommodating the diversity of student learning styles. Through a qualitative research design with a descriptive case study approach, this study involved 28 students as subjects. Data were collected through triangulation methods, namely a comprehensive diagnostic assessment, participant observation, in depth interviews with lecturers and students, and analysis of Semester Learning Plan (RPS) documents. The results of the diagnostic assessment empirically mapped the learning style profiles of the 28 students into three main neuro-cognitive preferences: visual dominance (13 students), auditory (8 students), and kinesthetic (7 students). The research findings indicate that the implementation of differentiated learning was executed systematically through three essential instructional dimensions. In the content differentiation dimension, lecturers adjusted the format of teaching materials to be multimodal (interactive digital text, infographics, podcasts, and short videos). In the process differentiation dimension, the orchestration of the Project Based Learning and Flipped Classroom models was applied. In the differentiation dimension, students are given autonomy to produce assignment outputs in the form of academic essays, literary appreciation, or observational videos/vlogs. This strategy has been empirically proven to increase students’ academic engagement, intrinsic learning motivation, and comprehensive understanding of language materials, while also deconstructing the historical stigma that Indonesian language courses are monotonous and dogmatic. Further discussion of this study highlights that the effectiveness of the differentiation strategy highly dependent on the pedagogical competence of lecturers as curriculum designers, facilitators, and innovators, even though in practice they are faced with the challenges of high administrative burdens and time constraints.